Balance Board-based System for Fall Prevention in Older Adults - Carlos Miguel Dias de Brito (2015)
The increase in quality of life over the past century led to the growth of life expectancy, which turns population increasingly older. With this change, age related problems are more common. One of these problems is falls and their grave consequences. As age degrades biological elements that control body balance, falls become more frequent and more severe. Fall prevention programes usually integrate several complementary methods. One of them is exercise that improves balance in older adults, decreasing fall risk, but also strengthens the body, mitigating fall consequences. However, motivating seniors to do healthy exercises is difficult. Recent affordable motion sensing devices have been shown to bring motivation as they turn physiotherapy sessions into entertaining and engaging interactive environments. One of those, the Nintendo Wii Balance Board System (WBB), uses four pressure sensors that measure the user's center of pressure (COP) which computation has been proved to be useful in helping the therapists evaluate their patient's balance. Many of these devices were created with entertainment purposes through exergames, which are video games where the player needs to do exercise to play. When oriented to therapy, exergames can be more motivating for patients than traditional rehabilitation methods. The main objective of this dissertation is to study the relation between older adults and interactive exergames to provide a solution for their poor motivation towards regular exercise practice. In addition, the WBB capabilities are explored in order to evaluate the player's balance automatically through COP related metrics, which can help supervisors monitor patients. An alliance of game development techniques with fall-prevention exercises may motivate older adults as it combines the pleasure of playing video games with the need to promote balance. Two interactive exergames were developed. These games require using the WBB to perform exercises that are part of the main fall-prevention programs, such as Otago Exercise Programme or Fitness and Mobility Exercise (FAME), and balance assessment scales as well, such as Berg Balance Scale. While the senior plays the game, the system uses the WBB capabilities to track the COP and compute balance assessment metrics used by physiotherapists, namely the COP's mean velocity and total oscillation. This data can be further processed and COP's path, amplitude over time and frequency maps can be generated. The system was evaluated with two separate set of tests with a total of 17 volunteers, in which they had the chance to interacted with the games. Although most of them did not fully understand the games' mechanics and logic t their first attempt, all of them stated they enjoyed the experience, would like to play regularly and that the exergames motivated them to do exercise. The developed solution can hopefully lead seniors to increase the practice of physical activity and eventually decrease fall risk while providing physiotherapists a mean to monitor the evolution of balance of their patients.